Post-divorce parental conflict, economic hardship and academic achievement among adolescents of divorced families - Esmaeili, Nooshin Sabour; Yaacob, Siti Nor; Juhari, Rumaya; Mansor, Mariani (Canadian Center of Science and Education, 2011)
This study focuses on the relationships between post-divorce parental conflict, economic hardship and adolescents’ academic achievement among 800 adolescents (424 girls and 376 boys) aged 15 to 18 years from divorced families. The instruments used for data collection were the Post-divorce Parental Conflict and Economic Hardship scales. In conclusion, the results obtained from the current study revealed that post-divorce parental conflict and economic hardship had significant relationships with adolescent academic achievement among divorced families. Post-divorce parental conflict and economic hardship may affect parental quality that consequently leads to poor parent-adolescent relationship. Poor parent-adolescent relationships adversely influence adolescent functioning.